Potential use of Janus structures in food applications. Issue 6 (23rd March 2022) - Subasi, Busra Gultekin; Xiao, Jianbo; Capanogluo, Esra
Abstract : Janus surfaces present technological opportunities both for research and industry in which different chemical, physical and/or structural components need to coexist for a single purpose such as chemistry, textile and material science. Varying inorganic and organic (polymer‐based) materials are conventionally used however, utilizing nature‐derived polymers to fabricate Janus structures is a recent and attractive trend which makes them more applicable for bio‐based treatments with environmental concerns. Particularly, promising applications of Janus structures as being surfactants, drug delivery and micro/nano encapsulation vehicles for biomedical purposes successfully forward the interest on Janus concept to the food related practices. Producing Janus structures from nature‐derived and food grade polymers such as alginate, cellulose, chitosan, lipid nanocrystals, zein and some plant‐proteins and their usage stronger emulsions with higher stabilities, biosensing or antimicrobial practices as well as bioactive delivery and release control might be considered as a new era for food processing industry.